Identifying the Type of a Contract to Transfer Health Services to Charities in Teaching Hospitals of Shahid Beheshti University of Medical Sciences in Tehran, Iran - Mahmud Nayeri; Somayeh Hessam; Amir Ashkan Nasiripour; Katayoun Jahangiri (Baqiyatallah University of Medical Sciences, 2020)
Background: One of the most important issues in the health system is to provide the necessary resources to present health services. To increase the role of charities and facilitate public participation in the treatment area and to develop hospital units, the cooperation between charity organizations and public hospitals must be highlighted. Objectives: This study aimed at identifying the type of contract for the transfer of health services to charities in the teaching hospitals of Shahid Beheshti University of Medical Sciences in Tehran, Iran. Methods: This study was conducted in hospitals of Shahid Beheshti University of Medical Sciences in 2019. The statistical population of the study consisted of 411 people, including managers, chiefs, and deputies, contracting experts, hospital social workers, managers and lawyers of the university, trustees, and managers, and charity experts. The research sample consisted of 330 people who were selected using a stratified random sampling method. SPSS version 18 and AMOS software were used to analyze the data. Results: By identifying the selection criteria of a charity to operate in the hospital, identifying the contract model, identifying the share of capital and current costs, and selecting the type of department in the contract with path coefficients of 0.78, 0.72, 0.68, 0.73, and 0.73, respectively, it can be ensured that the costs of an inpatient ward were supplied by the charity during the contract term. Conclusion: The study showed that the partnership contract model is the most appropriate type of contract in the transfer of health services to charities.